NATIONAL SPECIFICS OF THE LINGUISTIC MEANS OF SMILE REPRESENTATION IN ENGLISH AND RUSSIAN (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-10-20The relevance of this study is determined by the interest of scientists in the culturally determined specifics of the phenomenon of a smile and by the need for a contrastive analysis of the linguistic means representing it in English and Russian with the involvement of explanatory and phraseological dictionaries as well as language corpora.The aim of the work is to identify the national specifics of the means of representing the phenomenon of smiles in English and Russian.The study made it possible to identify national-specific means of representing the phenomenon of a smile, which can be divided into three groups: 1) means present only in one language and reflecting the specifics of culture; 2) means present only in one language and indirectly expressing the specifics of culture, in particular, the significance of a smile; 3) means present in both languages and correlated with one denotatum, but differing in the technique of secondary nomination.Among the first are the means in English that emphasize the importance of an optimistic attitude to life, the value of a smile, the obligatory presence of a smile under any circumstances, the connection of a smile with the key concept of individualistic Anglo-Saxon culture “privacy” and with the sense of humor important for the English-speaking society. In Russian such means include units that condemn excessive smiling, reflect the direction of a smile only to pleasant people but not to everyone and show the connection of a smile with the collectivist character of Russian culture. The second group includes such English units as smiler, wear nothing but a smile, plumber's smile. The third group includes pairs of phrases that accentuate different features of the same denotatum.The results of the study can be used by specialists dealing with the problems of lexicology, translation or intercultural communication.Key words: contrastive analysis, national specifics, culture, individualism, collectivism, emotions, smile